The cytochrome c peroxidase and cytochrome c encounter complex: The other side of the story. Issue 10 (12th April 2014) - Schilder, Jesika; Löhr, Frank; Schwalbe, Harald; Ubbink, Marcellus
Abstract : Formation of an encounter complex is important for efficient protein complex formation. The encounter state consists of an ensemble of orientations of two proteins in the complex. Experimental description of such ensembles inherently suffers from insufficient data availability. We have measured paramagnetic relaxation enhancements (PRE) on cytochrome c peroxidase (CcP) caused by its partner cytochrome c (Cc) carrying a spin label. The data complement earlier PRE data of spin labelled CcP, identifying several new interactions. This work demonstrates the need of obtaining as many independent data sets as possible to achieve the most accurate description of an encounter complex. Abstract : The CcP–Cc encounter complex was studied with paramagnetic NMR. MTSL spin labels were attached to Cc and PRE was observed in the CcP spectrum. Our data matched the previous encounter complex model well, with a few exceptions. Novel interactions were observed that were not seen in previous studies. This highlights the importance of obtaining a comprehensive data set.